Childcare and parental leave - NU. CEPAL (ECLAC, 2014)
This issue of Challenges examines the progress made thus far on childcare leave for parents —mothers and fathers— and turns a spotlight on pending debts in this regard. Few legislative or practical measures exist for satisfying the many types of early childhood care needs, and inequalities of origin are still rife. In order to meet those needs, the policy response must be aimed at ensuring universal satisfaction of children's right to care regardless of the formal employment status (or otherwise) of their parents, and the existing models of care from birth must be thoroughly reviewed.